2017
DOI: 10.1051/978-2-7598-1949-2
|View full text |Cite
|
Sign up to set email alerts
|

The ESPAS e-infrastructure: Access to data from near-Earth space

Abstract: University College London (UCL) has conducted research on the upper atmosphere of the arctic auroral regions since the 1960s, contributing with both observational and modelling studies. In terms of observations, UCL has designed and built its own Fabry-Pérot Interferometer (FPI) instruments and deployed a network of these in Northern Scandinavia since the beginning of the 1980s. Meanwhile on the modelling side, UCL has developed so-called General Circulation Model (GCM) of the upper atmosphere/ionosphere coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Significant electron precipitation occurs at these latitudes during magnetospheric storms due to increased electron scattering into the bounce loss cone. However, the bounce loss cone at these latitudes is significantly larger than the 30 • field of view of the POES telescopes (Asikainen, 2019;Rodger et al, 2013). This means that the POES 0 • detectors do not resolve fluxes near the edge of the loss cone in the case of partially filled loss cones.…”
Section: Methodsmentioning
confidence: 94%
“…Significant electron precipitation occurs at these latitudes during magnetospheric storms due to increased electron scattering into the bounce loss cone. However, the bounce loss cone at these latitudes is significantly larger than the 30 • field of view of the POES telescopes (Asikainen, 2019;Rodger et al, 2013). This means that the POES 0 • detectors do not resolve fluxes near the edge of the loss cone in the case of partially filled loss cones.…”
Section: Methodsmentioning
confidence: 94%
“…Note, however, that the data processing used here is based on the raw MEPED data and not on the processing methodology described by Green (2013). The corrections and calibrations introduced to the MEPED measurements have been documented by Asikainen andMursula (2011), Asikainen et al (2012), and Asikainen and Mursula (2013). Figure 1a shows a schematic of a POES satellite orbit along with the directions of SEM-1 and SEM-2 telescopes superposed on the same satellite.…”
Section: Datamentioning
confidence: 90%
“…However, Raben et al (1995) state that the +Y axis would point opposite to the satellite velocity like in SEM-2. In the process of recalculating all auxiliary data (e.g., telescope pitch angles) dependent on satellite location (Asikainen, 2017) both satellite coordinate system definitions were tested. It was found that the original pitch angles stored in the SEM-1 data records are consistent with the Raben et al (1995) definition, which will thus be used here.…”
Section: Datamentioning
confidence: 99%
“…The energetic particle measurements from the MEPED instrument onboard the NOAA/POES satellites currently form the most important long-term data set providing information about precipitation of energetic electrons and protons into Earth's atmosphere. Previous work on this data set has solved many problems related to instrument degradation and calibration and has greatly improved the quality of the data (Asikainen, 2017;Asikainen & Mursula, 2011, 2013Asikainen et al, 2012). Based on these previously corrected energetic electron measurements, we here first composed from each satellite the daily averaged latitude distribution of electrons in three integral energy channels, two nearly orthogonal telescopes, two opposite MLT sectors, and two hemispheres.…”
Section: Discussionmentioning
confidence: 99%